Willingness to use a drug checking service for cannabis and cannabis-based products: results from an online survey of people who regularly use cannabis in France - Martin Bastien; Salim Mezaache; Cécile Donadille; Laélia Briand Madrid; Maëla Lebrun; Victor Martin; Perrine Roux (Harm Reduction Journal)
Abstract Introduction As cannabis is illegal in France, there is no regulation of the quality or composition of cannabis products on the illicit market. Although access to drug checking services for people who use drugs (PUD) is possible in several harm reduction (HR) structures for a large number of illicit substances, these structures seldom have the tools needed to adequately analyze organic substances such as cannabis. Methods We conducted an online survey among people who use cannabis. The survey questionnaire collected data on respondents’ socio-demographic characteristics, use of cannabis and other psychoactive substances, and their willingness to use a cannabis drug checking service. We constructed a multivariable logistic regression model to explore factors associated with the latter dimension. Results Among the 553 participants included in the analyses, 73.4% said they would be willing to use a cannabis checking service. Self-identifying as a woman was negatively associated with the desire to use such a service (ORa [95% CI] = 0.54 [0.35–0.86]). In contrast, having a tertiary education level (ORa [95% CI] = 2.14 [1.45–3.17]) and declaring therapeutic use of cannabis (sometimes/often: ORa [95% CI] = 1.71 [1.09–2.69]; always: ORa [95% CI] = 2.61 [1.25–5.49]) were positively associated factors. Conclusions Our results highlight the strong willingness of many people who use cannabis in France to control the quality of the cannabis they obtain, particularly persons who use cannabis for therapeutic reasons. The implementation of adequate cannabis checking services in HR structures must take into account the diversity of populations that consume cannabis; in particular, they should be designed in such a way as that more women and persons with a lower level of education will use them.